Genomic islands of differentiation between house mouse subspecies - Harr, Bettina (Genome Research, 2006)
Understanding the genes that contribute to reproductive isolation is essential to understanding speciation, but isolating such genes has proven very difficult. In this study I apply a multilocus test statistic to >10,000 SNP markers assayed in wild-derived inbred strains of house mice to identify genomic regions of elevated differentiation between two subspecies of house mice, Mus musculus musculus and M. m. domesticus. Differentiation was high through ∼90% of the X chromosome. In addition, eight regions of high differentiation were identified on the autosomes, totaling 7.5% of the autosomal genome. Regions of high differentiation were confirmed by direct sequencing of samples collected from the wild. Some regions of elevated differentiation have an overrepresentation of genes with host–pathogen interactions and olfaction. The most strongly differentiated region on the X has previously been shown to fail to introgress across a hybrid zone between the two subspecies. This survey indicates autosomal regions that should also be examined for differential introgression across the hybrid zone, as containing potential genes causing hybrid unfitness.